EFFECTIVENESS OF COMMUNICATION CHANNELS FOR MATERNAL HEALTHCARE IN DELTA STATE - OZIWELE, Eloho Patience (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
This study on the effectiveness of communication channels for maternal healthcare is one of great concern with the increased health risks for women in their reproductive years of pregnancy and childbirth. This is especially true in developing countries such as Nigeria where thousands of women die yearly in pregnancy or childbirth. The qualitative and quantitative design method was applied in the study and the questionnaire was used for data collection from 399 respondents. The study found that the level of awareness of the programmes was encouraging for FMHCP and HeFAD; that the communication channels were adequate, and more than half thought they were effective in influencing participation in the maternal healthcare programmes. The findings provide healthcare professionals with an important insight into issues of effective communication therefore, recommend the continuous usage of communication channels to spread awareness of maternal healthcare programmes to enhance the provision of appropriate health information and maternity care to women.